1991
DOI: 10.1103/physrevb.43.8850
|View full text |Cite
|
Sign up to set email alerts
|

Thermal vibration and melting from a local perspective

Abstract: X-ray-absorption fine-structure (XAFS) measurements of lead from' 10 K through and above the melting transition at 600 K have been carried out. A cumulant expansion analysis provides data on the first four moments of the radial distribution of the first shell, which are used to construct a consistent temperature-dependent radial distribution function for the solid. The distribution is one given by a simple one-dimensional anharmonic oscillator. The results also demonstrate that XAFS, a local probe, can clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(179 citation statements)
references
References 15 publications
7
170
1
1
Order By: Relevance
“…For weak thermal disorder, the temperature dependence of the lowest-order cumulants can be expressed in terms of the force constants of the pair potential (6). In Dalba & Fornasini (1997), the classical approximation of Tranquada & Ingalls (1983) and Stern et al (1991) has been reported.…”
Section: Pair Potential Energymentioning
confidence: 93%
“…For weak thermal disorder, the temperature dependence of the lowest-order cumulants can be expressed in terms of the force constants of the pair potential (6). In Dalba & Fornasini (1997), the classical approximation of Tranquada & Ingalls (1983) and Stern et al (1991) has been reported.…”
Section: Pair Potential Energymentioning
confidence: 93%
“…The best fit values of 2 0 S were found to be 0.873 (14) and 0.947 (19), respectively. In order to break the correlation between the amplitude factors in the fit, the 2 0 S parameter of the NPG was fixed to that of bulk Au (0.873).…”
Section: Data Processing and Analysismentioning
confidence: 94%
“…19,20 In the next Section we present experimental details on synthesis, scanning electron microscopy characterization and EXAFS measurements of NPG. Section III describes the data processing and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…19 In another study, ∆σ 2 of lead increases linearly with temperature (10 -4 Å 2 /K) up to the melting temperature. 41 The Debye-Waller factor for large clusters should be chosen lower than for smaller clusters, because the structural disorder is lower. We have shown that it is important to measure series of catalysts, so that trends can be identified.…”
Section: Fitting Exafs Data Collected At Elevated Temperaturesmentioning
confidence: 99%